A Tale of Two Somali Community-Based Organizations in Cairo: Between Assistance, Agency &Community Formations - Huser, Hannah (AUC Knowledge Fountain, 2014)
Based on ethnographic field research in two Somali refugee- and migrant-initiated community-based organizations (CBOs) in Cairo, I look at their role in community formations, assistance to refugees and creating linkages to service providers to refugees. Moreover, I explore the CBOs as sites of individual agency and as expressions of collective action at the organizational level. CBOs have been explored from various conceptual angles, including networking, social capital, and integration. The manifestation of CBOs can be influenced by endogenous and exogenous factors, raising questions as to where CBOs can be located between genuine sites of identity construction and community-building and their externally-induced fabrication as such. Individual and collective agency cannot be removed from the internal and external structural conditions and power dynamics either. A comparison of the two CBOs under investigation shows that community formation at the organizational level can manifest itself in various forms. Somalis’ identity construction, based on the mutually influencing factors of refugeeness and soomaalinimo, inform understandings of community and the role of the CBOs in it. At the same time, the spatial location of CBOs as well as CBO-internal dynamics can influence notions of community and the nature of community enactment. Moreover, the CBOs exhibit different forms of decision-making structures as well as degree of institutionalization which influences the position and agency of actors within them. Overall, the CBOs can be seen as sites of community formation and allow their members to exert agency by defying notions of the helpless and dependent refugee. The CBOs fulfill various functions as providers of education, assistance and information and as linkages between Somali refugees and refugee service providers. Their degree of institutionalization, however, influences the way they are acknowledged and supported by humanitarian actors. The findings show that community outreach approaches of institutions such as UNHCR and other NGOs can provide opportunities as well as risks for CBOs depending on their position inside or outside the humanitarian framework. It urges us to look at how current approaches prioritize certain outlooks of CBOs over others, thereby dismissing the important functions of less structured and more locally-situated CBOs. Against the background of restrictive rights, limited livelihood opportunities and minimal assistance for refugees in cities such as Cairo, and the recognition that camp-based models are largely ineffective in urban refugee settings, the research is a timely contribution to exploring CBOs as sustainable community-based formations of support and alternatives to the mainstream humanitarian regime. The research, thereby, shows that CBOs cannot be seen as unitary entities, but can take differing forms, and functions for their members, highlighting the importance of flexible approaches towards CBOs when viewing them as actors within urban refugee contexts.